DISEMINASI TATA KELOLA ADMINISTRASI DIGITAL DI WILAYAH PEMERINTAHAN DESA ABUSAKIM BENGKULU TENGAH DALAM MENUNJANG DESA CERDAS - Novi Rahayu; Marsidi Marsidi; Askani Askani; Erlian Dwisnu; Rudi Hartono (Jurnal Semarak Mengabdi, 2023)
This charity event (PKM) was held in Abu Sakim Village, Pondok Klapa District, Bengkulu Central Governorate. The method used is Participatory Learning and Practice Process (PLA). The purposes of this non-commercial service implementation are to:1) Support the development of village management utilizing village technology. 2) As the main database and information for managing village government and village development in Abu Sakim, provide village officials with an understanding of proper and correct village government management. The results of these PKM are:1) Abu Sakim village officials understand the appropriate leadership management of the village as per the guidelines of the Minister of Home Affairs Decree No. 47/2016. 2) Abu Sakim village officials already know how to digitally process and operate village administration, paving the way for smart villages.